ANALISIS RISIKO PRODUKSI, HARGA, DAN PENDAPATAN USAHATANI KENTANG DI DESA NGADUMAN, KABUPATEN SEMARANG - Gregorius Adi Nugroho Saputro; Tinjung Mary Prihtanti (Agros Journal of Agriculture Science, 2023)
Ngaduman Village, Getasan District, Semarang Regency, located at an altitude of 1800 meters above sea level, is a center for vegetable crops. Farmers in Ngaduman Village plant potatoes in April with a monoculture cropping system. This study aims to analyze the risk level of production, price, and income in potato farming, and to find out the efforts made by farmers in dealing with production, price, and income risks in potato farming. The data used are primary and secondary data, the data collection technique is a survey through interviews. The sampling technique uses a purposive sampling method, with a total sample of 30 farmers. Production, price and income risk analysis techniques use the Coefficient of Variation (CV), while the efforts made by farmers to overcome risks use a qualitative descriptive approach. The coefficient of variation (KV) which shows the risk of potato production is below 1, meaning low risk, where the KV of potato production is 0.3. The coefficient of variation (KV) indicating the risk of potato prices is 0.03. The coefficient of variation (KV) of potato farming income risk is 0.55. To deal with production risks, it is necessary to spray pesticides regularly to minimize pest and disease attacks and include a planting season schedule with reference to weather changes. Meanwhile, to deal with price risk, farmers carry out price comparisons and sell to collectors at the most appropriate price and face income through efforts to reduce production costs, including through the use of their own manure and utilizing the remaining harvest as seeds for the next planting season.INTISARI Desa Ngaduman Kecamatan Getasan, Kabupaten Semarang berada di ketinggian 1800 mdpl merupakan sentra tanaman sayuran. Petani di Desa Ngaduman menanam kentang pada bulan April dengan sistem tanam monokultur. Penelitian ini bertujuan menganalisis tingkat risiko produksi, harga, dan pendapatan usahatani kentang, serta mengetahui upaya yang dilakukan petani dalam menghadapi risiko produksi, harga, dan pendapatan dalam berusahatani kentang. Data yang digunakan data primer dan sekunder, teknik pengambilan data adalah survei melalui wawancara Teknik pengamblian sampel menggunakan metode purposive sampling, dengan total sampel 30 petani. Teknik analisis risiko produksi, harga, dan pendapatan menggunakan Coefficient of Variation (CV), sedangkan upaya yang dilakukan petani mengatasi risiko menggunakan pendekatan deskriptif kualitatif. Koefisien Variasi (KV) yang menunjukkan risiko produksi kentang dibawah 1, artinya risiko rendah, dimana KV produksi kentang 0,3. Koefisien Variasi (KV) yang menunjukkan risiko harga kentang 0,03. Koefisien Variasi (KV) risiko pendapatan usahatani kentang 0,55. Untuk menghadapi risiko produksi maka perlu dilakukan penyemprotan pestisida secara berkala untuk meminimalisir serangan hama dan penyakit serta memuat penjadwalan musim tanam dengan acuan perubahan cuaca. Sedangkan untuk menghadapi risiko harga, petani melakukan perbandingan harga dan menjual kepada pengepul dengan harga yang paling sesuai dan menghadapi pendapatan melalui upaya menekan biaya produksi, antara lain melalui pemakaian pupuk kandang sendiri dan memanfaatkan sisa panen sebagai bibit untuk musim tanam selanjutnya.